Migratory pattern in the genus Circus: sex and age differential migration in Italy - Gustin, Marco; Pizzari, Tommaso (Ornis Svecica, 1998)
The migratory patterns of Marsh Circus aeruginosus, Pallid C. macrourus, and Montagu's C. pygargus Harrier were studied in spring in south-east Italy. Differences in the time of passage during the season were found between sexes and age classes in all three species. Adult males showed a significant tendency to migrate earlier than females and the latter earlier than juveniles. Also, adult Marsh and Montagu's Harriers passed significantly earlier during the day than second calendar year individuals. Such patterns are explained in the light of the selective pressure exerted on adults to reach the breeding territories early in the reproductive season.